Accommodation of Excess Oxygen in Group II Monoxides. Issue 1 (29th September 2012) - Middleburgh, Simon C.; Lagerlof, Karl Peter D.; Grimes, Robin W.; Ching, W.‐Y.
<x xml:space="preserve">Abstract</x> Atomic scale simulations are used to predict how excess oxygen is accommodated across the group II monoxides. In all cases, the preference is to form a peroxide ion centered at an oxygen site, rather than a single oxygen species, although the peroxide ionic orientation changes from <100> to <110> to <111> with increasing host cation radius. The enthalpy for accommodation of excess oxygen in BaO is strongly negative, whereas in SrO it is only slightly negative and in CaO and MgO the energy is positive. Interestingly, the increase in material volume due to the accommodation of oxygen (the defect volume) does not vary greatly as a function of cation radius. The vibrational frequency of peroxide ions in the group II monoxides is predicted with the aim to provide test data for future experimental observations of oxygen uptake. Finally, calculations of the dioxide structures have also been carried out. For these materials the oxygen vacancy formation energy is always positive (1.0–1.5 eV per oxygen removed) indicating that they exhibit only small oxygen defect concentrations.